Visual Analysis of Research Status and Trends of Motivational Factors in Second Language Acquisition: 二语习得中动机因素的研究现状与趋势的可视化分析 - Xiangning, Li (Published by Confucius Institute UNS, 2024)
In order to more intuitively analyze the research status and research trends of motivational factors in second language acquisition, this paper summarizes and combs through all the relevant articles included in the CNKI database from 2009-2024 with the help of the Citespace tool, and analyzes the number of articles, research hotspots, and research trends in the field through keyword co-occurrence, cluster analysis, keyword time-zone diagrams, and other visualization methods. It is found that (1) the number of articles published on motivational factors in second language acquisition is generally cyclical, with fluctuations, but overall the number of articles is relatively stable; (2) the research hotspots in this field are centered on the research hotspots of English language learning, dynamics, influencing factors, and online learning; and (3) since 2020, the study of international postures, changes in motivational dynamics and retrospectives is emerging as a new direction in the study of motivational factors.